Neotaphonomic insights from modern owl pellets in the Ararat Depression (Armenia): Implications for Middle Paleolithic microvertebrate accumulations - Dominik L. Rogall; Hugues-Alexandre Blain; Tsovinar Hovhannisyan; Andranik Gyonjyan; Gor Kaloyan; Boris Gasprayan; Ariel Malinsky-Buller (Archaeological and Anthropological Sciences, 2026)
Predator-accumulated microvertebrate assemblages preserve high-resolution records of past ecosystems, yet their interpretation requires robust modern analogues. Here, we present the first neotaphonomic study of owl pellets from the Ararat Depression (Armenia), a key biogeographic corridor of the Armenian Highlands. By comparing modern prey assemblages accumulated by the Eurasian Eagle-owl ( Bubo bubo ) and the Little Owl ( Athene noctua ), we evaluate predator-specific taphonomic signatures and their implications for interpreting Middle Paleolithic microfaunal deposits. Taxonomic, skeletal, and digestive data were quantified. Results show clear distinctions between B. bubo and A. noctua accumulations in prey spectrum, fragmentation, and digestion intensity, with (A) noctua producing highly fragmented and prey-restricted assemblages, and (B) bubo yielding more diverse and less altered remains. These taphonomic results are then utilized to evaluate environmental indices (Taxonomic Habitat Index, Habitat Weighting Method) in order to reconstruct prey habitats. Application of these modern analogues to Holocene and late Pleistocene deposits at Ararat-1 Cave and Kalavan-2 reveals that A. noctua is a potential accumulator at Ararat-1 during the Holocene, while mixed signals at Ararat-1 Cave and Kalavan-2 open-air site during the Pleistocene suggest additional taphonomic agents. Importantly, the owl-derived faunal signal consistently indicates open steppe–shrubland environments with only limited woodland cover. This refines previous, more general environmental reconstructions by providing a taxon-specific, predator-mediated perspective on local habitats at the scale of human occupation, a line of evidence that has not previously been applied in the Armenian Highlands. Together, these results establish a foundational neotaphonomic framework for the region and demonstrate how modern owl assemblages can refine archaeological interpretations and paleoenvironmental reconstructions.